Practical palliative care course for doctors in specialist training. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Nicholson, Alex; French, Ann
Abstract : Background: National directives (Supportive and Palliative Care: NICE 2004, End of life strategy: DoH 2008), National Service Frameworks for long-term conditions and Medical Specialty Training curricula have created demand for education of the medical workforce in palliative and end of life care. Traditional methods include seconded attachments spent with palliative care services including hospices, but expanding demands/expectations require alternative methods to deliver education and experience. Aims: Building on success of an initiative for GPs, a course designed and run through Teesside University seeks to meet training needs of hospital doctors throughout the North East aspiring to become consultants in any discipline. Four palliative medicine consultants act as tutors albeit without formal funding. Several Deanery specialty training committees recognise the course as fulfilling necessary requirements. The course is rated Level 5 (Diploma) and provides 30 credits. Success awards a Certificate in Professional Development. Delivered partly through the virtual learning environment and partly through clinical placement the course comprises: 10 weekly on-line 'lessons' addressing key topics including objectives, reference material and a formatively reviewed assignment. 10 clinical sessions matching identified learning needs, arranged by the learner and linked to a reflective diary A group ethics tutorial The final summative assessment is a 4000 word reflective piece of writing demonstrating integration of learning from all course components into personal professional development. Conclusion: Eighty-seven training grade doctors have enrolled since 2005. Formal evaluation (of 2005 and 2006 cohorts) and informal evaluation annually is positive. Graduates report high levels of satisfaction and impact. Modifications have been made in response to comments. A recurring concern is the difficulty in securing clinical placements due to competing pressure on palliative care services from other professional visitors. This is frustrating given that the underlying ambition is to enhance the skills in the 'generalist' workforce.